2014
DOI: 10.1016/j.rbmo.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of blastocysts biopsied and vitrified once versus those cryopreserved twice for euploid blastocyst transfer

Abstract: Trophectoderm biopsy with comprehensive chromosome screening (CCS) has been shown to increase implantation and pregnancy rates. Some patients desire CCS on previously cryopreserved blastocysts, resulting in blastocysts that are thawed/warmed, biopsied, vitrified and then warmed again. The effect of two cryopreservation procedures and two thawing/warming procedures on outcomes has not been effectively studied. Cycles were divided into two groups: group 1 patients underwent a cryopreserved embryo transfer with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 20 publications
4
29
0
Order By: Relevance
“…There has been a recent significant increase in the frozen embryo replacement (FER) cycles not only due to the availability of surplus embryos but also due to cryo-all cycles to avoid the risk of ovarian hyperstimulation syndrome [1], preimplantation genetic screening [2], and concerns for detrimental effect of controlled ovarian stimulation on endometrial receptivity in a fresh cycle [3]. The 2011 results, published in 2016, generated from European registers by ESHRE reported that the proportion of FER cycles was 32.3 % [4] compared to 28 % in 2010 [5].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a recent significant increase in the frozen embryo replacement (FER) cycles not only due to the availability of surplus embryos but also due to cryo-all cycles to avoid the risk of ovarian hyperstimulation syndrome [1], preimplantation genetic screening [2], and concerns for detrimental effect of controlled ovarian stimulation on endometrial receptivity in a fresh cycle [3]. The 2011 results, published in 2016, generated from European registers by ESHRE reported that the proportion of FER cycles was 32.3 % [4] compared to 28 % in 2010 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al (15) reported a live birth after transfer of blastocysts that were frozen and thawed twice using a slow-freezing protocol. Taylor et al (7) recently demonstrated that previously cryopreserved blastocysts could be successfully warmed, biopsied, revitrified, and rewarmed, and the survival rate of rewarmed blastocysts was 87.5%. In our study, of the 19 twice-warmed blastocysts, 18 (94.7%) survived the second warming.…”
Section: Discussionmentioning
confidence: 99%
“…Wininger et al (6) reported a case of pregnancy after the blastocysts were rebiopsied following allele dropout after an initial biopsy at day 3. Most recently, Taylor et al (7) reported the rebiopsy of three test-failure blastocysts in two PGS cycles. After rewarming, two rebiopsied blastocysts survived but resulted in no pregnancy.…”
mentioning
confidence: 99%
“…The use of vitrification is being tested to determine if freezing all embryos in routine IVF 9 cycles gives a higher success rate, as it allows for optimization of the endometrium (Roque et al, 2015). These freeze-all cycles, open up the opportunity to freeze all embryos post biopsy for PGD (Schoolcraft et al, 2011, Taylor et al, 2014b. This relaxes the time constraints on the PGD team to perform the diagnosis and allows batching of samples, both of which make the test significantly cheaper and improves the quality of the test results.…”
Section: Developments In Artmentioning
confidence: 99%